Plio–Quaternary Tectonic Activity in the Northern Nubian Belts: The Main Driving Forces - Enzo Mantovani; Marcello Viti; Daniele Babbucci; Caterina Tamburelli (Applied Sciences)
It is suggested that the occurrence of tectonic activity in the northern Nubian belts (Tell-Rif and Atlas systems) since the Late Pliocene can be interpreted as one of the processes that were produced in the central and western Mediterranean zones by the collision of the Adriatic continental promontory with the Anatolian–Aegean Tethyan system. Since then, the consumption of the residual low-buoyancy domains in the Mediterranean area was allowed by a major change in the plate mosaic and the related kinematics. The new tectonic setting started with the decoupling of a large portion of the Adriatic domain (Adria plate) from Nubia, through the formation of a long discontinuity crossing the Ionian domain (Victor Hensen–Medina fault) and the Hyblean–Pelagian domain (Sicily channel fault system). Once decoupled, the Adria plate underwent a clockwise rotation, at the expense of E–W shortening in the Hyblean–Pelagian domain and in the northern Nubian margin. The shortening in the Pelagian domain was accommodated by the northward escape of the Adventure wedge, which in turn caused the northward displacement of the eastern Maghrebian sector. The indentation of these structures into the Alpine–Apennine material lying east of the Corsica–Sardinia block induced an east to southeastward escape of wedges (southern Apennines and Calabria). This occured at the expense of the remnant Ionian Tethys oceanic domain and the thinned Adriatic margin. The extensional regime that developed in the wake of the migrating wedges led to the formation of the central and southern Tyrrhenian basins. In the northern Nubian belts, the westward push of the Adria–Hyblean–Pelagian domain has been accommodated by oroclinal bending, thrusting and uplifting across the Tell and Atlas belts. This geodynamic context might explain some features of the seismicity time pattern observed in the Tell system.